Comparison of Birth Outcomes by Gestational Diabetes Screening Criteria - Esa M. Davis; Christina M. Scifres; Kaleab Abebe; Tina Costacou; Diane Comer; Patrick Catalano; Hyagriv Simhan; Matthew Freiberg; Nancy Day (Thieme Medical Publishers, Inc., 2018)
Abstract Objectives This study is to examine the association between different diagnostic criteria for gestational diabetes mellitus (GDM) and adverse birth outcomes. Study Design A retrospective cohort study of 5,937 women with a singleton pregnancy was conducted, who completed GDM screening between 24 to 32 weeks gestational age. Four nonoverlapping groups of women defined as: 1) Normal: glucose challenge test (GCT) <130 mg/dL, 2) elevated GCT + normal oral glucose tolerance test (OGTT): abnormal 1 hour GCT + normal 3 hour OGTT, 3) GDM/International Association of Diabetes in Pregnancy Study Group (IADPSG): abnormal 3 hour OGTT by the IADPSG criteria, and 4) GDM/Carpenter-Coustan (CC): diagnosis per CC criteria. We used logistic regression to examine the association between GDM group classification and main outcome of macrosomia and secondary birth outcomes. Results Prevalences were GDM/CC 4.6%, GDM/IADPSG 3.0, and 7.6% overall. GDM/IADPSG group was associated with increased macrosomia (adj OR [odd ratio] 1.87; 95% CI [confidence interval]: 1.08-3.25; p = 0.02), while GDM/CC group was associated with increased preterm birth (adj OR 1.75; 95% CI: 1.05-2.80; p = 0.03). Conclusion Little difference in birth outcomes was found between the two criteria, GDM/CC and GDM/IADPSG. Randomized controlled trials are needed to clarify the risks and benefits of these screening paradigms before their incorporation into clinical practice.